Value Potential of Ethical Education in the Information Age - Aziza, Xamidova; Tuychiyevna, Razikova Lola (Research Parks Publishing LLC, 2023)
The article analyzes modern ethical education in higher education from the point of view of its axiological potential. It is assumed that ethical education can become one of the ways to solve the actual problem of the crisis of moral values in the process of digitalization. The philosophical and pedagogical prerequisites for ethical education are described; considers the values that can be transmitted in the process of teaching ethics; the relevance of ethical education in the information age is substantiated. The scientific novelty of the article is determined by the axiological approach to the analysis of the content of ethical education and the definition of the prospects for ethical education in terms of its value potential. As a result, the main problems of modern ethical education are revealed, ways of expanding its axiological content are outlined.